Real life super heroes - Fezzani, Nadia, 1976- (desLibris. Books collection., 2017)
"Dressed like heroes from comic books and action movies, real life super heroes are out there. They dress up at night, fight crime, save people, and some of them even have secret identities. Are they ordinary, mild-mannered citizens ̥or are they larger-than-life characters, determined to fight crime, risking life and limb to defend victims of violence and injustice? And why do some choose to reveal their true identities, while others prefer to remain anonymous? Guided by a reporter's instincts and a thrill-seeking nature, journalist Nadia Fezzani set out in search of the secret lives of these men and women, who put themselves in harm's way to protect their fellow human beings. Through interviews and patrols with these super heroes, she discovers what lies behind their activities. Now, after facing gunmen and other dangers on patrol, she brings a psychologically fascinating look at this world of vigilantes."--